Methods for designing all‐dielectric frequency selective surface via dielectric materials. Issue 10 (4th July 2017) - Li, Liyang; Wang, Jun; Wang, Jiafu; Ma, Hua; Yan, Mingbao; Feng, Mingde; Du, Hongliang; Zhang, Jieqiu; Qu, Shaobo
Abstract : In this paper, we propose methods for designing all‐dielectric frequency selective surface (FSS) by using microwave dielectric materials. Dielectric materials with relative permittivity of 3.75–960 are employed for designs. The design methods work efficient in framework of dielectric resonator theory. By adjusting the permittivity and thickness of the dielectric materials, band‐stop response can be designed at frequencies from 3 to 80 GHz. To design FSSs using different dielectric materials, there clearly shows a rule to keep the x ‐ o ‐ y cross sectional size of the unit cell still, simultaneously to keep the magnetic and electric resonant modes stable inside the dielectrics. The variation relationship of the fractional bandwidth with the ratio of the wavelength and the periodic size is concluded. The rule is workable for dielectric materials with the most relative permittivities. This paper provides significant methods of using nearly all possible dielectric materials to design all‐dielectric FSS with a quite simple structure in the desired frequencies.